?????????? ?????????????? ?????????????? ???? ???????????? ???????????? - Agus Aulia Elluthfi; Bakhrum (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2022)
Interpretation of The Meanings of The Quran (Tafsir) and Rhetoric (Albalagah) are two closely related. Both of them are complement each other in understanding the intent and meaning of the verses the Al-Quran. This research try to describe the history of the development bookkeeping of litearature Tafsir from the classical period to the Ottoman Turkish dynasty. This research method is Analytical Descriptive. The results of the research show that the bookkeeping of Tafsir has passing through 4 important phases. First one is the prophetic era,then shahabah era,next to Tabiin era, and the era after Tabiin. In the era Phase after Tabiin emerge of school tafsir such as islamic jurisprudence based Interpretation Tafsir, science based tasir, phylology based tafsir, etc. corresponding to characters, backgrounds, tendencies of the Authors of Interpretation of Tafsir. Most phylology based Authors referred to Tafsir Al-Kasyaf that belongs to Azzamakhsyari, also to Tafsir Arrozi and Tafsir Albaidhowi in their phylology based tafsir writings. As for the writing of tafsir literary in the modern era, especially during the Ottoman dynasty, there's a progress was marked by some a famous author such as Abu Assaud through his Tafsir Irsyadul Aql Assalim.